EFEKTIFITAS EKSTRAK KULIT DUKU (Lansium Domesticum) SEBAGAI INSEKTISIDA NABATI DALAM MEMBUNUH NYAMUK Aedes spp TAHUN 2014 - ika juni; wirsal hasan; nurmaini * (Lingkungan dan Kesehatan Kerja, 2015)
Abstract Aedes spp is vectors of any diseases such as dengue, phylariasis, chikungunya and yellow fever. Control of transmission of diseases is by control the vector of disease. One of efforts is by using toxic synthetic insecticide on human so it need the safe bio insecticide. The method applied in this research is complete random sampling in which the experiment with 3 treatments and one control, the spraying with concentration of extract duku (Lansium domesticum) peel for concentration 0%, 05%. 1% and 1.5% by 3 repetition. The result of research indicates that on the observation during 30 minutes, the number of dead mosquito is differed on each concentration. On concentration 0.5% the death is 42%, concentration 1% is 56% death, concentration 1.5% is 82% the death and on control with concentration 0% there is not the death of Aedes spp. For observation during 24 hours indicates that the death for concentration 0.5%, 1%, 1.5% and 0% is 44%, 62%, 89% and 0%, respectively. The conclusion of this research is the concentration of duku peel extract (Lansium domesticum) that kill the Aedes spp is concentration of 1% with the death of mosquito is 60% in the observation for 30 minutes.